2015
DOI: 10.1073/pnas.1421035112
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Bada and Cleaves: Ab initio free-energy landscape of Miller-like prebiotic reactions

Abstract: In their letter addressing a recent ab initio density-functional theory-based study of Miller-like experiments (1), Bada and Cleaves (2) downplay the role of formamide, citing its half-life, lower than that of HCN, and the fact that the calculations were performed in aqueous phase rather than in gas phase. Miller's original experiment had both gas and condensed phases but ab initio modeling of a full biphasic system was beyond the scope of ref. We are factual about what we observe: Strecker's reactants, within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…., R Nf , whereas z is a measure of the distance from the pathway itself. This class of variables proved crucial to obtain free energy landscapes of a variety of processes including gas-phase chemical reactions with concerted mechanisms (33)(34)(35) and transformations of carbon nanostructures (36). The key ingredient of path collective variables, determining their effectiveness in a given problem, is the definition of distance DðRðtÞ, R k Þ between the atomic configuration at time t and the k th reference structure.…”
Section: Methodsmentioning
confidence: 99%
“…., R Nf , whereas z is a measure of the distance from the pathway itself. This class of variables proved crucial to obtain free energy landscapes of a variety of processes including gas-phase chemical reactions with concerted mechanisms (33)(34)(35) and transformations of carbon nanostructures (36). The key ingredient of path collective variables, determining their effectiveness in a given problem, is the definition of distance DðRðtÞ, R k Þ between the atomic configuration at time t and the k th reference structure.…”
Section: Methodsmentioning
confidence: 99%
“…Although these additional simulations showed that the application of an electric field is capable of decreasing the height of the free-energy barrier, the fact that a significant finite barrier still persists at a strong field intensity of 0.50 V/Å witnesses that the choice of the simple interatomic distance between species forming either C-N or C-C bonds does not represent a good choice for the reproduction of the complex multidimensional free-energy landscape. This way, additional simulations performed by means of metadynamics techniques clarified some of these crucial aspects [ 82 ]. Further DFT-based and metadynamics simulations were executed in direct connection with more recent Miller–Urey-like experiments by Ferus et al [ 20 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…This concept is summarized in Figure 1. This reactions cascade can take place in bulk formamide in significantly boosted in presence of mineral phases in the reaction environment [13][14][15][16][17][18][19][20]. Such catalytic effect does not only affect the nucleobases productivity, but also causes its selective conversion toward specific products depending on the nature of the mineral component.…”
Section: Introductionmentioning
confidence: 99%